PENDIDIKAN MULTIKULTURALISME DALAM AL-QUR’AN DAN PENERAPANNYA PADA PENDIDIKAN AGAMA ISLAM (ANALISIS DESKRIPTIF Q.S. AL-HUJURAT AYAT 13 PADA TAFSIR AL-MISBAH) - Ruhana Khoirun Annisa; Asmaji Mukhtar; Lilik Rohmat N; Ali Muktafi (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2020)
This study discusses the multiculturalism education contained in Q.S. Al-Hujurat verse 13 which contains concepts, values, and their application in Islamic religious education, with the formulation of the problem: (1) How is the concept of multiculturalism education contained in Q.S. Al-Hujurat verse 13? (2) What are the educational values of multiculturalism contained in Q.S. Al-Hujurat verse 13?, (3) How is the application of multiculturalism education contained in Q.S. Al-Hujurat verse 13 on Islamic religious education? This research is a qualitative research that uses a descriptive analysis approach. Then the data analysis uses data reduction and content analysis regarding the sources taken, and the achievement is assisted by the supervisors. The research analysis explains that: the concept of multicultural education contained in Q.S. Al-Hujurat verse 13 is the creation of humans of the same kind and in pairs, humans are created as nations and tribes, know each other, and have piety. The values contained in the Q.S. Al-Hujurat verse 13 humans must recognize gender equality and equality, know each other, be pious, and tolerate. While its application in Islamic religious education is to apply the concepts and values of multiculturalism education contained in Q.S. Al-Hujurat verse 13 in daily life, mutual respect and respect among others despite different beliefs, getting to know each other so that they can share experiences and learning, complement each other, and be kind. This is all done so that the Indonesian state can produce a generation that is multicultural and cultured and upholds the value of diversity.